Cracking Behavior, Microstructure and Properties of Selective Laser Melted Al-Mn-Mg-Sc-Zr Alloy - Ziyu Zhai; Wei Pan; Bo Liang; Yantao Liu; Yongzhong Zhang (Crystals, 2022)
In this paper, the cracking of Al-Mn-Mg-Sc-Zr alloys prepared by selective laser melting (SLM) was comprehensively explored and the influence of process parameters on the generation and propagation of cracks was deeply studied. It was found that the higher laser power and volume energy density will lead to a decrease in the relative density of the material. The lower laser power or volume energy density will lead to cracking of the alloy. The microstructure analysis indicated that plenty of manganese-rich second phases precipitated at the bottom of the melt pool, which increased the tendency of cracking occurred at the bottom of the melt pool. Through the optimization of the process parameters, the SLM forming process parameters of the Al-5.22Mn-1.16Mg-0.81Sc-0.46Zr alloy are successfully obtained, and the crack-free tensile samples are prepared. The microstructure and mechanical properties of the as-deposited aluminum-manganese alloy is analyzed. The bottom and inside of the melt pool are equiaxed grains. The size of the equiaxial grains at the bottom of the melt pool is less than 2 μm, and the coarse equiaxial grains inside the melt pool are approximately 5 μm. As-deposited alloy has a room temperature tensile strength of 455.2 ± 0.7 MPa and elongation of 15.4 ± 0.3%. This study provides guidance for selective laser melting forming of high-strength aluminum-manganese alloy parts, and promotes the industrial production of high-strength aluminum alloy near net forming complex parts.